The symbiosis between LVMH and the Paris 2024 Olympic Games: A case study on value co-creation in an urban context - Vázquez Sacristán, Isabel A.; Rodríguez Hernández, Marina (Street Art & Urban Creativity, 2025)
The study examines the synergy between LVMH and the city of Paris in the context of the 2024 Olympic Games. Using tools like Instagram and Google Trends, it investigates how LVMH has leveraged the global attention on the French capital to enhance its brand image. Preliminary results show a significant increase in searches related to LVMH and its brands, highlighting the effectiveness of this strategy. The research emphasizes the mutual benefits of this strategic collaboration, reinforcing Paris's position as a global hub for fashion and luxury while consolidating LVMH's leadership in the sector. Theoretically, the study contributes valuable insights to the fields of sports marketing and sponsorship, providing lessons for other organizations seeking similar partnerships.